William Blake Poem “A Poison Tree”: Element Analysis - Luh Kadek Dwi Windari (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Literature is one of the important things in language. There are various types of literary works, one of it is poetry. Poetry is defined as a literary work used by the author as a medium in expressing all the imagination, feelings, or emotions of the author. The process of casting imagination is done by adding supporting elements of poetry to give an element of beauty to each line of poetry. This analysis aims to find out the element that contain the poem titled “A Poison Tree” by William Blake. This research is used descriptive qualitative to describe all the elements that found in the poem. Based on the result, there are nine elements found including the imaginary, the metaphor, the symbol, the paradox, the allusion, the meaning and idea, the tone, the rhyme, and the rhythm.